2000
DOI: 10.1159/000008243
|View full text |Cite
|
Sign up to set email alerts
|

A 52-Week Study of the Efficacy of Rivastigmine in Patients with Mild to Moderately Severe Alzheimer’s Disease

Abstract: The efficacy of a centrally active cholinesterase inhibitor, rivastigmine tartrate (ENA 713; Exelon®), in patients with mild to moderately severe Alzheimer’s disease was evaluated in a 26-week open-label extension of a 26-week, double-blind, placebo-controlled study. By 52 weeks, patients originally treated with 6–12 mg/day rivastigmine had significantly better cognitive function than patients originally treated with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
185
0
7

Year Published

2003
2003
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(203 citation statements)
references
References 7 publications
11
185
0
7
Order By: Relevance
“…These studies suggest that improved memory-associated synaptic plasticity may be the fundamental mechanism underlying the disease modifying action of drugs such as AChEIs (Farlow et al, 2000). In support of this, in Alzheimer's disease, for example, there is a striking upregulation of NCAM polysialylation, but not NCAM polypeptide, in the dentate molecular layer (Gillian et al, 1994;Mikkonen et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These studies suggest that improved memory-associated synaptic plasticity may be the fundamental mechanism underlying the disease modifying action of drugs such as AChEIs (Farlow et al, 2000). In support of this, in Alzheimer's disease, for example, there is a striking upregulation of NCAM polysialylation, but not NCAM polypeptide, in the dentate molecular layer (Gillian et al, 1994;Mikkonen et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Recent data suggest that patients who discontinue treatment with cholinesterase inhibitors have a significantly delayed cognitive decline as compared to patients receiving placebo (Farlow et al, 2000). Such observations suggest AChEIs to provide a disease-modifying effect as well as symptomatic relief and, moreover, that this benefit remains after drug withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…For example, delayed-start clinical trials in patients with mild to moderately severe AD (baseline MMSE scores, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] indicate that any delay in the initiation of treatment with ChE inhibitors may result in irretrievable loss of benefit compared with patients receiving treatment earlier in the disease course. Two 52-week studies 9,93 were conducted, with an initial 26-week placebo-controlled phase followed by a 26-week, openlabel extension study during which all patients received rivastigmine. In addition to providing symptomatic benefit in patients with mild to moderate AD 9 and more severe disease, 93 the results confirm that rivastigmine treatment may modify the natural progression of the disease.…”
Section: Potential Effects On Disease Progressionmentioning
confidence: 99%
“…Two 52-week studies 9,93 were conducted, with an initial 26-week placebo-controlled phase followed by a 26-week, openlabel extension study during which all patients received rivastigmine. In addition to providing symptomatic benefit in patients with mild to moderate AD 9 and more severe disease, 93 the results confirm that rivastigmine treatment may modify the natural progression of the disease. Patients initially treated with placebo failed to "catch up" with those individuals who received the drug for the full 52 weeks (Figure 3).…”
Section: Potential Effects On Disease Progressionmentioning
confidence: 99%
“…The effect exerted by AChEis use in this study is comparable to previously reported randomized and open-label placebo controlled trials. In fact, the majority of these trials, using either donepezil, rivastigmine or galantamine, demonstrate an initial improvement in cognitive performances during the first 12 weeks, returning to close to or baseline levels at the end of the treatment period (Farlow et al, 2000;Raskind et al, 2000;Rogers et al, 2000;Tariot et al, 2001). These studies show that the mean effect of the drug over placebo represents an improvement in cognition roughly equivalent to stemming 6-12 months of natural decline in untreated patients (O'Brien and Ballard, 2001).…”
Section: Discussionmentioning
confidence: 99%